2022
DOI: 10.3389/fgene.2022.905824
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Soil-Derived Covariates in Progeny Testing and Line Selection to Enhance Genomic Prediction Accuracy in Soybean Breeding

Abstract: The availability of high-dimensional molecular markers has allowed plant breeding programs to maximize their efficiency through the genomic prediction of a phenotype of interest. Yield is a complex quantitative trait whose expression is sensitive to environmental stimuli. In this research, we investigated the potential of incorporating soil texture information and its interaction with molecular markers via covariance structures for enhancing predictive ability across breeding scenarios. A total of 797 soybean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
(81 reference statements)
2
5
0
Order By: Relevance
“…Similar results were described by Canella Vieira et al. (2022), showing that soil texture can explain a great proportion of the phenotypic variation in annual crops. Furthermore, using Gaussian kernels, it was possible to identify the soil covariates across locations (Figure 1) and the relationship (SRM) between them (Figure 2), group the locations via a k ‐means clustering approach (Figure 3), and visualize how the multi‐environment trials as distributed in the Mississippi Delta (Figure 4).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results were described by Canella Vieira et al. (2022), showing that soil texture can explain a great proportion of the phenotypic variation in annual crops. Furthermore, using Gaussian kernels, it was possible to identify the soil covariates across locations (Figure 1) and the relationship (SRM) between them (Figure 2), group the locations via a k ‐means clustering approach (Figure 3), and visualize how the multi‐environment trials as distributed in the Mississippi Delta (Figure 4).…”
Section: Resultssupporting
confidence: 89%
“…However, the success of such studies relies heavily on the quality and quantity of data used. One factor that can significantly impact the accuracy of plant breeding studies is the incorporation of soil‐derived covariates (Canella Vieira et al., 2022). These covariates, which include soil nutrient content, moisture levels, and pH, can greatly affect plant growth and development (Poggio et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The soil conductivity measurements were expected to be a proxy for local variation in water holding capacity, which could have affected yield in a dry season. It was anticipated that these covariates would account for a portion of the environmentally-induced variation in observed yields, as found by Vieira et al (2022) . However, despite variation in soil conductivity across the fields in each trial, no detectable relationship to the yield variation was found.…”
Section: Discussionmentioning
confidence: 99%
“…The high availability of environmental data in testing locations has resulted in a thorough characterization of environmental effects over the observed phenotype. In addition to the traits commonly measured by plant breeders, data from weather stations, soil surveys, and public repositories has been recently integrated into genomic prediction (GP) models (Malosetti et al 2016; Monteverde et al 2019; Canella Vieira et al 2022).…”
Section: Introductionmentioning
confidence: 99%